Source extension region scaling for AlGaN/GaN high electron mobility transistors using non-alloyed ohmic contacts. (August 2016) - Takhar, Kuldeep; Akhil Kumar, S; Meer, Mudassar; Upadhyay, Bhanu B.; Upadhyay, Pankaj; Khachariya, Dolar; Ganguly, Swaroop; Saha, Dipankar
Highlights: Extensive scaling of source extension region using non-alloyed ohmic contact for improved RF performance. Existence of optimum source extension length due to competing effects of source resistance and parasitic capacitance. Design rule for source extension length for a given sheet resistance and parasitic capacitance. Abstract: Here we have demonstrated AlGaN/GaN based high electron mobility transistors with scaled source extension regions using non-alloyed ohmic contacts to two-dimensional electron gas (2-DEG). We show that the scaling of the extension region has profound impact on the device radio frequency (RF) response and the performance peaks at an optimum extension region length. The unity current gain ( fT ) and power gain frequencies ( f max ) have been found to be 79.6 and 96.2 GHz, respectively, for a 260 nm gate length ( Lg ) and 120 nm extension region length. The devices show a very large fT  ×  Lg product of 20.7 GHz μm at the optimum extension length. The presence of the optimum extension length and the equivalence of source extension and gate length scaling may serve as additional design rules for high performance HEMTs.